The Role of Sales Accounting Information System in PT. Petro Gasindo Intiniaga - Galih Supraja (Future Science, 2023)
The role of sales accounting information systems in a company is very important Importantly, having a sales accounting information system can maximize profits obtained, achieve sales volume, and support sales growth. So that If the company achieves maximum sales levels, the company needs to pay attention sales system in the company. This research focuses on (1) How the sales accounting information system is implemented at PT. Petro Gasindo Intiniaga, (2) What is the internal control system at PT. Petro Gasindo Intiniaga (3) What is the role of the sales information system at PT. Petro Gasindo Intiniaga to improve the internal control system. This research uses a qualitative approach with a descriptive research type. The data sources used are Primary Data and Secondary Data. Research procedure The data used is field search (a) interviews (b) documentation (c) Observation. To check the validity of the data findings, three triangulations were carried out (1) source triangulation (2) technique triangulation (3) time triangulation. The result of this research is an internal control system in Information Systems Sales Accounting at PT. Petro Gasindo Intiniaga is not doing well. In the The company still has several weaknesses, including; (1) There still exists a dual function in the sales system, between the warehouse helper function and admin functions which are only carried out by the warehouse department. (2) The Authorization System for Approval for Delivery of goods is still authorized by the production and warehouse departments. (3) Deep sales system in which the cash received is not fully deposited into the bank on the date the transaction takes place.